Adjusting Fitts’ Paradigm for Small Touch-Sensitive Input Device with Large Group of Users - Kim, Inki; Jo, Jang Hyeon (Proceedings of the Human Factors and Ergonomics Society Annual Meeting, 2012)
Fitts’ paradigm is a classic theory to describe the relationship between movement time, distance and accuracy for rapid aimed movement. Generally speaking, it describes the Speed-Accuracy Tradeoff (SAT) along task condition as well as along users. A controlled factorial experiment is conducted for small touch-sensitive input device to observe SAT relationship within task condition and large number of users. Fitts’ paradigm did not successfully model the SAT relationship, due to ambiguous definition of accuracy index and lack of variables to reflect subject bias. Fitts’ paradigm was adjusted by revising accuracy index appropriate for direct finger input, and by introducing a trajectory variable to keep track of the subject bias. It raised the model fit (R2) from 0.523 to 0.833 for a model of task condition.